Combination of dietary glycaemic index and fasting time prior to slaughter as strategy to modify quality of pork. (March 2020) - Rey, A.I.; Menoyo, D.; Segura, J.; López-Bote, C.J.; Calvo, L.
Abstract: This study evaluates the effect of the dietary glycaemic index (low: L-GI vs. high: H-GI ), pre-slaughter fasting times (17 h: f 17 vs. 19 h: f 19 vs. 22 h: f 22 ), and their interaction, on certain meat quality characteristics. Greater duration of fasting resulted in lesser drip loss of muscle, greater LIPE expression (lipolysis) and 10% greater TBARS, with PUFA being the main source of free-fatty acid production. L-GI diets produced a greater drip loss, lipolytic activity and lesser C18:1n-9 relative mobilization, suggesting this group had greater glycolytic potential than H-GI. An interaction was found in meat characteristics related to fat metabolism. The IRS2 gene expression was greater in pigs fed L-GI diets, but only in a low fasting period. LIPE gene expression was greater for L-GI-f 17 group than for L-GI-f 22 . Lesser n-6 PUFA but greater MUFA were found in the free fatty acid fraction of L-GI- f 17 group thus resulting in a faster lipolysis initiation in this group.